2016
DOI: 10.1515/nbec-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Molybdate-reducing and SDS-degrading Enterobacter sp. Strain Neni-13

Abstract: Toxicants removal through microorganism’s action is intensely being sought due to economic reasons. The aim of this paper is to isolate a bacterium that is able to reduce molybdenum blue and at the same time can grow on the detergent Sodium Dodecyl Sulfate (SDS). Biochemical analysis resulted in a tentative identification of the bacterium as Enterobacter sp. strain Neni-13. Growth on SDS showed a 100 % removal at 800 mg/L SDS within 12 days. The removal of SDS from media was confirmed through Methylene Blue Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…There are various reports describing the isolation of bacteria having the capacity to degrade surfactants, including a wide variety of Pseudomonas strains ( Klebensberger et al, 2006 ; Chaturvedi and Kumar, 2011a ; Yeldho et al, 2011 ; John et al, 2015 ), Klebsiella oxytoca ( Shukor et al, 2009 ; Masdor et al, 2015 ), Enterobacter sp. strain NENI-13 ( Rahman et al, 2016 ), and finally microbial consortia composed of Acinetobacter calcoaceticus and Pantoea agglomerans ( Abboud et al, 2007 ). However, these microorganisms were selected from environments highly contaminated solely with detergents with no other xenobiotics present.…”
Section: Introductionmentioning
confidence: 99%
“…There are various reports describing the isolation of bacteria having the capacity to degrade surfactants, including a wide variety of Pseudomonas strains ( Klebensberger et al, 2006 ; Chaturvedi and Kumar, 2011a ; Yeldho et al, 2011 ; John et al, 2015 ), Klebsiella oxytoca ( Shukor et al, 2009 ; Masdor et al, 2015 ), Enterobacter sp. strain NENI-13 ( Rahman et al, 2016 ), and finally microbial consortia composed of Acinetobacter calcoaceticus and Pantoea agglomerans ( Abboud et al, 2007 ). However, these microorganisms were selected from environments highly contaminated solely with detergents with no other xenobiotics present.…”
Section: Introductionmentioning
confidence: 99%
“…8,17,37 Sulfurospirillum are sulfur-oxidizing bacteria that can outcompete sulfate-reducing bacteria for sulfate in the presence of nitrate, thereby reducing H 2 S production. 9,46 Similarly, a few Enterobacteriaceae have been found to reduce molybdate, 51,52 which may have provided a similar competitive advantage to these microbes. At the same time, molybdate is structurally similar to sulfate and inhibits the growth of H 2 S producers, 50 were present only at several timepoints in the nitrate microcosms.…”
Section: Mineral Supplements Control Metabolism and Shape Microbiome ...mentioning
confidence: 99%
“…Studies on the effect of heavy metal to the growth of the bacterium on SDS utilized the microtiter plate format [32,33]. The growth medium was as follows: Na2HPO4, (1.39 g l -1 ), KNO3, (0.5 g l -1 ), KH2PO4, (1.36 g l -1 ),MgSO4 (0.01 g l -1 ), CaCl2 (0.01 g l -1 ), and (NH4)2SO4 (7.7 g l -1 ) [29]. Then, SDS was filter sterilized using a filter syringe (0.2 µm) and added into the cooled medium to the final concentration of 1000 mg/L.…”
Section: Growth Of Sds-degrading Bacteriummentioning
confidence: 99%
“…There are few studies available that examine the effect of heavy metals on microbial growth, as most studies on this topic use primary models rather than secondary models. In this work, an SDS-degrading bacterium was isolated and it was found that heavy metals including mercury, silver, and mercury significantly inhibited its growth [29,30]. Using various inhibition models, the aim of this study was to investigate the effect of mercury on the growth rate of this bacterium when grown on SDS.…”
Section: Introductionmentioning
confidence: 99%